2009
DOI: 10.1002/joc.1944
|View full text |Cite
|
Sign up to set email alerts
|

Vertical moisture profile characteristics of severe surface drought and surface wetness in the western United States: 1973–2002

Abstract: Drought can be viewed as a three-dimensional phenomenon rather than simply a surface feature. We characterize drought across the western United States from 1973 to 2002 in a three-dimensional context by examining its vertical moisture extent using NCEP/NCAR Reanalysis data derived from rawinsonde moisture profiles. We then apply a discriminant analysis to establish the degree of difference between the vertical moisture profiles of extreme drought and extreme wetness conditions. The mean vertical moisture profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Juang et al (Juang et al 2007) found that convective precipitation over moist soils was typically greater in intensity and led to higher precipitation accumulation than for events over dry soil conditions. Garrity et al (Garrity et al 2010) studied the impact of extreme wet and dry regions over the western United States on atmospheric moisture profiles from reanalysis data. They found that the decrease of moisture during drought conditions was limited to below 700 mb and suggest that this may indicate that thunderstorms are playing a role in modulating droughts.…”
Section: Conceptual Model and Discussionmentioning
confidence: 98%
“…Juang et al (Juang et al 2007) found that convective precipitation over moist soils was typically greater in intensity and led to higher precipitation accumulation than for events over dry soil conditions. Garrity et al (Garrity et al 2010) studied the impact of extreme wet and dry regions over the western United States on atmospheric moisture profiles from reanalysis data. They found that the decrease of moisture during drought conditions was limited to below 700 mb and suggest that this may indicate that thunderstorms are playing a role in modulating droughts.…”
Section: Conceptual Model and Discussionmentioning
confidence: 98%
“…Discriminant analysis is a statistical technique that objectively classifies categories on the basis of a set of variables. Comparison with the objective classification derived from the linear combination of a set of variables reveals the extent to which an a priori classification scheme which might have been subjectively derived is reproducible [e.g., Diab et al ., ; Michailidou et al ., ; Garrity et al ., ]. Using the below 600 m agl wind speed maximum, above‐core wind shear and below‐core wind shear as the discriminating variables (the same as those presented in the LLJ detection scheme; Table ), the technique was used to objectively reclassify the profiles into the two classes.…”
Section: Llj Detection Criteriamentioning
confidence: 99%